Evaluation of antibiotic prescribing for ambulatory patients seeking primary dental care services in a public hospital in Ghana: a clinical audit study. Issue 4 (5th July 2022) - Sefah, Israel Abebrese; Sneddon, Jacqueline; Essah, Darius Obeng; Kurdi, Amanj; Fadare, Joseph; Jairoun, Ammar Abdulrahman; Godman, Brian
Abstract: Background: One in 10 of all antibiotic prescriptions globally are for dental conditions with 80% of them being inappropriate, making it a potential driver of antimicrobial resistance. Objectives: To evaluate the appropriateness of antibiotic use among ambulatory patients seeking dental care services in a public hospital in Ghana. Methods: A retrospective clinical audit was conducted by extracting the medical records of all patients seeking dental care at the ambulatory care clinic of Keta Municipal Hospital (KMH) from January 2020 to December 2020 using the hospital's electronic database. Descriptive statistics, bivariate and multivariate analysis were performed on the data collected. Results: Overall, 1433 patient medical records were extracted from the database within the study period. The mean age of the patients identified was 39.9 years with almost two-thirds being female. The majority (91.1%, n = 1306) of them were attended to by a dental nurse. In total, 88.6% ( n = 1269) of the patients received antibiotics and 87.5% ( n = 1254) of antibiotics prescribed were non-compliant with Ghana Standard Treatment Guidelines. Three-quarters of the dental conditions were managed with dual antibiotics comprising amoxicillin and metronidazole. Antibiotic prescription was associated with age, gender, type of prescriber and type of dental condition diagnosed. Conclusions: There is a high usage of antibiotics for dental conditions managed at the outpatient section of the hospital and most are inappropriate. Development of local guidelines supported by education of dental clinicians on empirical use of antibiotics is a suitable target for the antimicrobial stewardship team to address in KMH.